PARADIGMA ZAKAT PROFESI DALAM KEHIDUPAN MASYARAKAT GORONTALO - Kasim, Nur Muhammad (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2014)
This study aimed to explain the laws substances about the tithe of profession in law. To know the role of government on management and utilization tithe of profession. Moreover, want to know the people’s perspectives about tithe of profession in government management. Type of this study was the socio legal research by the use qualitative analysis technique and sourced of data from the primary data and secondary data, by using test model of frequency distribution. The result of research in substance there are weaknesses in the management of the tithe management. The role of government in management, and utilization tithe of profession was not maximized.The perception of Gorontalo society towards zakat profesi is still based on religion.